Peran platform e-learning dalam meningkatkan kemampuan literasi informasi di era digital - patikah, patikah02 (Maliki Interdisciplinary Journal, 2025)
This research aims to analyse the role of e-learning platforms in improving students’ information literacy skills in the digital era. With the development of technology, the use of e-learning becomes an alternative solution in a more flexible and interactive learning process. The method used in this research is a literature study, by reviewing various sources that discuss the effectiveness of e-learning in education. The results show that platforms such as Google Meet, Google Classroom, and Quizizz play an important role in supporting online teaching and learning activities. Google Meet helps to replace online face-to-face meetings, Google Classroom makes it easier to submit assignments, while Quizizz provides a more interactive and fun learning experience.